2016
DOI: 10.1039/c5ra26623h
|View full text |Cite
|
Sign up to set email alerts
|

Visible light photocatalysis with CBr4: a highly selective aerobic photooxidation of methylarenes to aldehydes

Abstract: An efficient, operationally simple, metal-free strategy for the selective oxidation of methylarenes to aromatic aldehydes through visible light photocatalysis employing CBr4 and molecular oxygen is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Furthermore, ap hoto-oxygenation reaction with 18 O 2 and H 2 18 Or evealed that the reaction did not involver adical chain propagation. [38] The catalyst was appliedt ov ariousm ethyl arenes bearinge lectron-donating (Me or OMe) and electron-withdrawing substituents (NO 2 ,F ,C l, Br,I ,C N, MeSO 2 ,a nd PhSO 2 )a nd showedg ood to excellent yield of the corresponding products.Am echanism based on a radicalp athway was also proposed.F irstly,C Br 4 generates a bromo radicalu nder irradiation with molecular oxygen.T his bromo radicalreacts with methylarene to generate benzyl radical 44 along with HBr.T he benzyl radicalt hen combines with O 2 to generate peroxy radical 45,w hich abstracts ah ydrogen atom from HBr and forms corresponding hydroperoxide species 46.T his hydroperoxides pecies eliminates H 2 Ot og ive the desired product 47 (Scheme 8). [37] Later,Y adav and co-workers developed CBr 4 -catalyzedo xygenationo fm ethyl arenest oa ldehydes.…”
Section: Direct Oxygenation Of Benzenes To Phenolsmentioning
confidence: 99%
“…Furthermore, ap hoto-oxygenation reaction with 18 O 2 and H 2 18 Or evealed that the reaction did not involver adical chain propagation. [38] The catalyst was appliedt ov ariousm ethyl arenes bearinge lectron-donating (Me or OMe) and electron-withdrawing substituents (NO 2 ,F ,C l, Br,I ,C N, MeSO 2 ,a nd PhSO 2 )a nd showedg ood to excellent yield of the corresponding products.Am echanism based on a radicalp athway was also proposed.F irstly,C Br 4 generates a bromo radicalu nder irradiation with molecular oxygen.T his bromo radicalreacts with methylarene to generate benzyl radical 44 along with HBr.T he benzyl radicalt hen combines with O 2 to generate peroxy radical 45,w hich abstracts ah ydrogen atom from HBr and forms corresponding hydroperoxide species 46.T his hydroperoxides pecies eliminates H 2 Ot og ive the desired product 47 (Scheme 8). [37] Later,Y adav and co-workers developed CBr 4 -catalyzedo xygenationo fm ethyl arenest oa ldehydes.…”
Section: Direct Oxygenation Of Benzenes To Phenolsmentioning
confidence: 99%
“…This is achieved using a metal-based catalyst and H 2 O 2 or molecular O 2 , which are clean oxidants, although with either low yields or poor selectivity. On the other hand, such limitations can be efficiently countered by using proper catalysts in combination with molar excesses of hypervalent iodine reagents or organic peroxides, which ultimately affect however the environmental cost of the whole process. Most of these methods require the use of transition-metal catalysts too. , We are unaware of reports on the direct oxidation of inactivated , benzylic methylenes to the corresponding carbonyls mediated by an organic acid catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanistic pathway, which may contribute to the reaction, involves the deprotonation of acidic radical cation D. It affords neutral radical F, which can be further oxidized either by Br radical or CBr4 leading to the desired product in its protonated form E. Detailed mechanistic studies on the role of CBr4 co-catalyst are ongoing, but preliminary results suggest that, through the photosensitized hydrolysis of CBr4, it may provide the starting concentration of bromide anions at the early stage of the process. Although the light-induced reactivity of this compound is usually associated with mesolytic bond cleavage, [52][53][54][55] or homolytic dissociation to CBr3 and Br radicals, 56,57 it has been shown that in the aqueous conditions the photoinduced hydrolytic pathway to HBr prevails. 58 Alternatively, the reduction of CBr4 by excited Ir(III)*-photocatalyst can be considered, leading to Br -, the CBr3 radical and Ir(IV)-complex.…”
Section: Resultsmentioning
confidence: 99%